Comparative study of haematological parameters of three sturgeon species in recirculating aquaculture system - Gultepe, Nejdet; Sazykina, Marina; Sazykin, Ivan; Sonmez, Adem Yavuz; Khmelectsova, Ludmila E.; Khammami, Margarita I. (Indian Journal of Fisheries, 2017)
The aim of this study was to evaluate and compare the haematological parameters of cultured Russian sturgeon (Acipenser gueldenstaedtii), stellate sturgeon (Acipenser stellatus) and Siberian sturgeon (Acipenser baerii) in recirculating aquaculture system. Total erythrocytes, thrombocytes, red blood cell distribution, monocytes, basophils as well as haemoglobin levels of stellate sturgeon differed significantly from that of the other two species (p